Making Open Access Viable Economically - Hyde, Andrew; Miller, Russell A.; Towfigh, Emanuel V. (German law journal, 2020)
The Editors-in-Chief have decided that we will provide our much-cherished readers with an editorial every so often as a way of sharing insights from the “machine room” where so much of the thinking and work is done to publish the German Law Journal. We want to let you in on the ideas that are on our minds, share with you our observations, and include you in the conversations we are having that might be of interest to you. We begin this tradition with this issue, Volume 21 – Number 6. Andrew Hyde, a member of the editorial team with which the Journal has partnered at Cambridge University Press, as well as Russell A. Miller and Emanuel V. Towfigh, two of the Journal’s co-Editors-in-Chief, open our From the Headquarters Essay with a piece on the Journal’s experiences with and its further plans for making open-access (OA) publishing economically viable. Related to that theme, we also want to share news with you about the introduction of a voluntary article processing charge this fall. Finally, we want to draw your attention to a videos and podcasts service we will start to produce to accompany the scholarship published in the Journal as a way of promoting our authors’ work and expanding access to their ideas. If you are interested only in these latter initiatives, you can also read the short section in the GLJ Instructions for Authors.